PENYISIHAN LOGAM BERAT DAN TSS PADA URBAN ROAD STORMWATER MENGGUNAKAN REAKTOR KONTINYU DENGAN MEDIA KOMPOS DAN TANAH - Fadhilah, Refnilda
The quality tests of urban road stormwater in Jl. Ir. H. Juanda, Bandung, provides information about the presence of heavy metals and Total Suspended (TSS) in urban road stormwater. The highest concentration of heavy metals in urban road stormwater are iron (Fe), manganese (Mn), copper (Cu) and zinc (Zn). The objective of this research is to determine the removal mechanism of these heavy metals and TSS with variety media compost and soil in a continuous reactor. A mixture of compost and soil is one of the media used in bioretention which is not yet known its removal mechanism of heavy metals and TSS. There are eight variations of the medium used are 100% of compost, 100% of soil, mixture of compost and soil with compost and soil ratio of 80:20%, 50:50%, and 20:80% and layer of compost and soil with compost and soil ratio of 80:20%, 50:50%, and 20:80%. For layers variation, the top layer is compost and the bottom layer is soil. Percentage ratio is the percentage of compost and soil mass. With debit 12 mL/min and retention time is 25 minutes, the results shown that the highest removal efficiency Fe, Mn, Cu and Zn using soil as media with removal efficiency for each parameter are 44.3-82.8%, 34.5-91.4%, 100%, and 86-97.3%. The highest removal efficiency of TSS also use soil media with efficiency values from 94.1 to 98.1%. The pH of stormewater is fluctuative for all of the reactors. The pH of treated stormwater ranges from 6 to 8. The mechanism of heavy metals removal that occurs in this process is adsorption and filtration mechanism. The mechanism of TSS removal that occurs in this process is adsorption mechanism.